HERMENEUTIKA HADIS ALA FAZLUR RAHMAN - Alma’arif, Alma’arif (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2015)
"> Fazlur Rahman was a very famous Islamic reformer. He was from Pakistan who previously had no contemporary thinkers such as Ahmad khan dan Sayyid Amir Ali and M. Iqbal. He mastered in turath and human sciences in Islamic studies. On the understanding of hadith, Rahman had an idea that the need for reevaluation of the diverse elements in the hadith and reinterpretation of a comprehensive and holistic to the elements in accordance with the moral - social conditions in the present. This can be done by historical studies and the Qur’an as a reference. It supposes be distinguished between the traditions of the historical and biography, that the traditions are supported by the facts of history, from technical traditions largely historical, the traditions that are not supported by historical facts validity.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />